Determining a wide range of antibiotics and pesticides in poultry feathers using selective accelerated solvent extraction-liquid chromatography-mass spectrometry. Issue 3 (23rd December 2021) - Wu, Huizhen; Zhou, Min; Xu, Jie; Wang, Jianmei; Tong, Jianying; Sun, Nabo; Qian, Mingrong
Abstract : This study established a detection method based on accelerated solvent extraction-liquid chromatography-mass spectrometry for determining residues of 3 chloramphenicols, 8 macrolides, 18 sulfonamides, 4 nitroimidazoles, 15 insecticides, and 22 fungicides in poultry feathers. Abstract : This study established a detection method based on accelerated solvent extraction-liquid chromatography-mass spectrometry for determining residues of 3 chloramphenicols, 8 macrolides, 18 sulfonamides, 4 nitroimidazoles, 15 insecticides, and 22 fungicides in poultry feathers. The extraction solvent, methanol, was used for a static extraction time of 5 min, and repeated three times. Fifty milligrams of adsorbents C18/PSA (1 : 1, W/W) were added to the extraction cell to achieve simultaneous extraction and purification. The extraction efficiency of three solvents, methanol, acetonitrile and ethyl acetate, was investigated. An orthogonal experimental design was used to explore the optimal combination of extraction temperature, static extraction time, number of extraction cycles, and adsorbent ratio for accelerated solvent extraction. After the optimal ratio was determined, the dosage of adsorbents was optimized. The extracted sample solution was concentrated by blowing nitrogen, redissolved, passed through a 0.22 μm PTFE membrane filter, then injected for instrumental analysis. The validation results showed that the recovery of the proposed method was 60.4–107.6%, the limit of detection 0.2–3.0 μg kg −1, and the limit of quantification 0.5–8.3 μg kg −1 . This quantitative multi-residue detection method was able to determine the residues of 70 target compounds in poultry feathers.